'Meet the New Boss … Same as the Old boss?' Technology, toil and tension in the agrofuel frontier. (July 2015) - Garvey, Brian; Tyfield, David; de Mello, Leonardo Freire
<x xml:space="preserve">Abstract</x> Agrofuels are increasingly sourced and sold as a socially and environmentally beneficial solution to oil dependence. The promotion of sugar‐derived ethanol as a substitute for petroleum has thus been key to state development and international trade policies by Brazil and the European Union, respectively, and subsequent investment by leading energy and food transnational corporations has transformed socio‐spatial relations in the new sites of production. Brazilian rural worker testimonies, however, point to large‐scale labour exclusion rather than reform and a deepening, rather than disruption, of historic power inequalities in the sector. Labour contestation challenges a converging institutional discourse of responsible technological innovation and social upgrading associated with emerging commodity chains and the 'green' economy. Although corporate and statutory response has been market‐orientated certification and 'more technology' the idea of the 'techno‐institutional fix' provides a power relation‐attentive analysis that invites the further exploration of socially committed alternatives to food and energy production.